Conversion and church : the challenge of ecclesial renewal : essays in honour of H.P.J. Witte - Witte, H., (Henk); Erp, Stephan van, 1966- (Brill's Studies in Catholic Theology, 2016)
Conversion is an important characteristic of religious renewal, and of the dialogue between churches and religious believers. In the Roman Catholic Church, conversion has played a significant role in ecumenical dialogue recently. It has become a challenge for the Church as a whole, instead of a call to individual believers alone. The contributors of this volume explore the different aspects of conversion in the history of theology, in the developments during and after the Second Vatican Council, in the Ignatian tradition, and in several ecclesial groups that have explored the opportunities of the ongoing renewal of the churches. Contributors are: André Birmelé, Inigo Bocken, Erik Borgman, Catherine Clifford, Peter De Mey, Adelbert Denaux, Eugene Duffy, Stephan van Erp, Joep van Gennip, Thomas Green, Wiel Logister, Annemarie Mayer, Jos Moons, Marcel Sarot, Karim Schelkens, Nico Schreurs, Matthias Smalbrugge, and Arnold Smeets.